The interaction of DNMT1 and DNMT3A epigenetic enzymes with phthalates and perfluoroalkyl substances: an in silico approach. Issue 5 (24th March 2023) - Innamorati, Giorgia; Pierdomenico, Maria; Benassi, Barbara; Arcangeli, Caterina
Abstract: The occurrence of long-lasting adverse effects of the environmental contaminants on human health is a current emerging issue. In particular, phthalates, poly- and perfluoroalkyl substances are proposed to trigger toxic effects as well as persistent changes on human development and metabolism by different mechanisms, including epigenetic modifications, although the specific underlying pathways are still unknown. This study contributes to identify the potential molecular initiating events of epigenetic-mediated adverse effects by an in silico approach, which combines molecular docking and molecular dynamics simulation. The approach probes the potential molecular interaction between several different phthalates and persistent organic pollutants and a specific class of epigenetic modulators, namely the DNA methyltransferases (DNMTs). The dynamics of interaction and the binding free energies of the ligand-DNMTs complexes demonstrated that pollutants can be classified into two main groups, according to the ligand-target complex stability: (1) a larger class of phthalates (DBP, DEHP, MBP and MEHP) acting as inhibitors of the enzymatic activity of the epigenetic targets and (2) a smaller class of phthalates (DMP and MMP) and perfluoroalkyl substances (PFOA and PFOS) which do not interact stably with the human DNMTs. These findings provide the first valuable in silico insights on the ability of these specific environmental pollutants to directly bind and inhibit a key class of epigenetic regulators. Communicated by Ramaswamy H. Sarma